Desenvolvimento e avaliacao empirica de um simulador educacional para o apoio ao ensino de ECG, baseado na orientacão espacial do coração. - PONTES, Paulo André Ignácio (Universidade Federal do Pará, 2018)
The electrocardiogram (ECG) is one of the most commonly used diagnostic procedures in medicine, so it is essential that undergraduate medical students learn to interpret it correctly while they are still in training. Of course, students go through classical learning (ex: lectures and lectures). However, they are generally not efficiently trained in ECG interpretation. In this regard, educational support methodologies and tools in medical practice, such as educational software, should be considered as a valuable approach for medical training purposes. This thesis deals with the development of a simulator (VETOECG) that allows experiential teaching, so that students can relate to projections of the cardiac electrical vectors, through the manipulation of the spatial orientation of the heart and the repercussions in their respective waves in the ECG. In addition, this thesis reports a formal experiment (pre / posttest with a randomized control group) to evaluate empirically the learning effetiveness of the tool and analyzes the subjective factors of students' perception regarding motivation, user experience and collected through questionnaires. The results indicated that the simulator has positive learning efficacy compared to traditional methodologies (statistically significant difference, p-value <0.0001 *, median of 38.5 points and interquartile range 23.1 to 46.2 points) used for learning in the proposed study. It can be verified that the simulator is adequate in the most diverse dimensions, since they were evaluated positively: in terms of motivation (88.15%), user experience (76%) and learning (96.5%).